Analysis of Atmospheric Conditions During Heavy Rain Using Adiabatic Lapse Rate in Tangerang City - Amalia, Rizkika; Ruhiat, Yayat; Septiyanto, Rahmat Firman (Universitas PGRI Semarang, 2025)
This study aims to understand the rate of temperature decrease in atmospheric conditions and determine the comparison between atmospheric stability and rainfall in Tangerang City using daily rainfall data and upper air data for the period 2019 to 2023. The data was obtained from Soekarno-Hatta Meteorological Station. The results of the analysis showed that the highest rainfall occurred in February 2020, with a total of 23 rainy days. In addition, lapse rate analysis indicates that atmospheric conditions are in a conditionally unstable state for 25 days. However, there is a difference between the number of rainy days and the number of days with unstable conditions, indicating that atmospheric instability does not always lead to precipitation. This study explains that although rain occurs under unstable atmospheric conditions, not all unstable conditions produce rain. Therefore, this study recommends the need for further studies to understand the complex interactions between meteorological factors that influence heavy rainfall phenomena in the region.Keywords: atmosphere, lapse rate, precipitation